SUPERVISI AKADEMIK BERBASIS NILAI-NILAI ISLAMI PADA SEKOLAH DASAR MODEL KOTA BANDA ACEH: (Suatu Analisis Humanisme Teosentris) - Khairullah (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2020)
Research on "Academic Supervision Based on Islamic's values in Model Elementary Schools of Banda Aceh (An Analysis of Theocentric Humanism)" was conducted in 2019. This research aims to describe, analyze or describe the practice of Islamic value-based supervision covering aspects of theocentric humanism carried out by school supervisors in three Model Primary Schools in Banda Aceh. School supervisors are important in the context of educational development with the supervision model that they run. This study seeks to see how the implementation of Islamic values is applied by supervisors to teachers. This research methodology is qualitative research by searching, analyzing, and making interpretation of data found through the results of documents, interviews and observations. The data that has been collected is checked for validity through the validity of the data in the form of trust. Data analysis technique is to reduce, present, and make conclusions from the results of research. The results of the study indicate that the implementation of academic supervision based on Islamic values has been carried out according to the basic assumptions in this study, although it is not comprehensive. Where, the supervisors carry out the pattern of supervision guidance by promoting democratic values that are full of dialogue, and far from the impression of inspection. Gentle, polite and humorous attitudes can be categorized as humanist values and sincerity and responsibility as theocentric values especially in the context of this study. Even so, this study offers a new model in the implementation of academic supervision based on Islamic values in the future as a form of concern in the realm of education, namely the supervision approach by promoting the principles of humanism and theocentricity as well as the attitude of compassion, courtesy, deliberation, knowledgeable, devoted, fair , authoritative, sincere and aim Rabbani in carrying out every stage of academic supervision.